Power circulation in driveline system when the wheels of tractor and trailer are driven - Janulevičius, Algirdas; Pupinis, Gediminas (Transport, 2013)
In off-road “tractor–trailer” vehicle combinations, the trailer can be equipped with one or more driving wheels. The distinguishing feature of vehicles with two or more driving axles is distribution of total power between the driving wheels. In machines with several driving axles, kinematic mismatch between theoretical wheel speeds nearly always takes place. The wheels of tractor and trailer can slip uniformly and differently, some of them may even slide. It is unfortunate when the wheels slide, as power circulation takes place. In this paper, power circulation of a vehicle composed of a tractor and trailer having driving wheels and driving wheels’ interaction with soil is investigated. The conclusion is that in a vehicle composed of two machines having two driven axles each, circulation of power can be avoided or reduced by turning off one driving axle in the machine, which delivers more power and has advancing driving wheels. First Published Online: 11 Oct 2013